Analysis of control systems for vehicle hybrid powertrains - Kliauzovich, Siarhei (Transport, 2007)
Ecological and socioeconomic factors determine high interest in the development of pollution‐free vehicles. At present use of electro‐vehicles is suppressed by a number of technological factors. Vehicles with alternative power‐trains are transitional stage between development of pollution‐free vehicles and vehicles with conventional internal combustion engine. According to these aspects the investigation on conventional hybrid drives and their control systems is carried out in the article. The equations that allow evaluating effectiveness of regenerative braking for different variants of hybrid drive are given. The AMESim software is used as the modeling environment, in which models of hybrid vehicles are developed and the results of virtual simulation are analyzed. Also a number of recommendations for increasing of regenerative braking effectiveness are given. First Published Online: 27 Oct 2010